Tempe Agroindustry Business Feasibility Analysis In High Village Village District Benai District Kuantan District (Case Study Of Mr. Iskandar's Tempe Agro-Industry) - Octha Levia; Meli Sasmi; Jamalludin Jamalludin (Fakultas Pertanian Universitas Muara Bungo, 2021)
This research was conducted in Tebing Tinggi Village, Benai Subdistrict, Kuantan Singingi Regency, which was conducted in April until August 2019. The purpose of this study was to determine the feasibility analysis of financial tempe agroindustry business (NPV, Net B / C, PBP, BEP) in the Village Tebing Tinggi, Benai District, Kuantan Singingi Regency. The result of the study of the feasibility analysis of Mr. Iskandar tempe agroindustry in Tebing Tinggi Village, Benai District, Kuantan Singingi Regency based on Net Present Value (NPV), Net B / C Ratio is very feasible to run, this can be seen in the Net Present Value (NPV) value of Rp 118.315.587,14, Net B / C Ratio value of 1.37. For Pay Back Period (PBP), Mr. Iskandar's tempe agroindustry business in 6 months 2 days. While the Break Even Point (BEP) of Mr. Iskandar's tempe agroindustry business in 5 years 25days.